Ageing Entrepreneurs and Business Transfer Challenges in Croatia - Mezulić Juric, Petra; Alpeza, Mirela; Oberman Peterka, Sunčica (Naše gospodarstvo/Our economy, 2022)
Business transfer as a research topic awakened the interest of researchers in the past few decades. Business transfer is defined as a change of ownership of any firm to another person or legal entity assuring the continuous existence and commercial activity of the enterprise, and it encompasses different kinds of transfers both to family and non-family members. Ageing and consequently retirement are often mentioned as the reasons for entrepreneurs’ exits from the companies and intention to initiate the business transfer process. A successful business transfer process is one of the key prerequisites for long- term sustainability of small and medium-sized enterprises. There is a significant number of ageing business owners in Croatia who will exit their companies in the coming years. Considering the number of these entrepreneurs and the influence their exits can have on company stakeholders and national economy in general, it is of great importance to better understand the factors that can influence the choice of their exit strategies. The aim of the paper is to provide an understanding of the dilemmas that the ageing entrepreneurs face when considering different exit modes. The data for the study was collected through in-depth, semi-structured interviews conducted with six ageing business owners. The analysis of the interviews enabled the identification of the challenges that ageing entrepreneurs face in the business transfer process: emotional attachment to the firm, strong preference for family succession and concerns about financial security after retirement. Some of these challenges are a result of the undeveloped business transfer ecosystem, strong tradition and cultural values that imply family succession as the only acceptable exit strategy for retiring company owners in Croatia.
Keywords: business transfer; entrepreneurial exit; ageing entrepreneurs; SMEs; business transfer ecosystem